Use of cytology centrifuged supernatants improves cost and turnaround time for targeted next generation sequencing. Issue 12 (22nd July 2020) - Gokozan, HamzaN.; Harbhajanka, Aparna; Bomeisl, Philip; Michael, Claire W.; Sadri, Navid
Abstract: BACKGROUND: Molecular testing is an essential step in providing patients with advanced non‐small‐cell lung cancer (NSCLC), the most appropriate front‐line targeted therapies. We recently implemented targeted NGS on previously discarded cytology centrifuged supernatant (CCS). METHODS: In this study, we reviewed our implementation process to evaluate its performance. Performance and turnaround time (TAT) of molecular testing on all cytology NSCLC cases submitted for targeted NGS from June 2018 to September 2019 were evaluated, which included 46 and 62 cytology cases before and after implementation of CCS, respectively. Associated cost savings using CCS was also analyzed. RESULTS: The mean TAT defined as the time of collection to time of reporting was 8.5 ± 1.8 days in CCS cohort (range 5‐13) as compared with 12.2 ± 5.3 days in the (FFPE) cell block (CB) cohort (range: 6‐27). The success rate of sequencing was similar for both cohorts (100% in CCS and 96% in FFPE CB). CONCLUSION: Our results demonstrate that NGS using CCS improves TAT, preserves FFPE CB for other testing, and results in cost savings of $50 per case.